2010
DOI: 10.1002/zoo.20302
|View full text |Cite
|
Sign up to set email alerts
|

Carnivorous mammals: nutrient digestibility and energy evaluation

Abstract: Estimating the energy content is the first step in diet formulation, as it determines the amount of food eaten and hence the concentration of nutrients required to meet the animal's requirements. Additionally, being able to estimate the energy content of a diet empirically known to maintain body condition in an animal will facilitate an estimation of maintenance energy requirements. We collated data on nutrient composition of diets fed to captive wild canids, felids, hyenids, mustelids, pinnipeds, and ursids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 86 publications
(69 reference statements)
2
64
0
Order By: Relevance
“…We did not account for potential differences in efficiencies of digestion and assimilation of salmon protein, salmon lipid, and oil in the experimental diet because these processes tend to be efficient in bears (Clauss et al 2010;Pritchard and Robbins 1990). However, digestion and assimilation can differ among nutrients and monomers of nutrients (e.g., FAs- Apgar et al 1987) and should be considered when making dietary inferences based on d 13 C breath values.…”
Section: Discussionmentioning
confidence: 97%
“…We did not account for potential differences in efficiencies of digestion and assimilation of salmon protein, salmon lipid, and oil in the experimental diet because these processes tend to be efficient in bears (Clauss et al 2010;Pritchard and Robbins 1990). However, digestion and assimilation can differ among nutrients and monomers of nutrients (e.g., FAs- Apgar et al 1987) and should be considered when making dietary inferences based on d 13 C breath values.…”
Section: Discussionmentioning
confidence: 97%
“…The digestive efficiency of brown bears is similar to those of obligate carnivores, and bears are not adapted to efficiently digest coarse forage [14]. Therefore, we used % dry faecal matter of faecal crude fibre content (FCF) and faecal protein content (FP) as proxies of diet quality in bears.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we used % dry faecal matter of faecal crude fibre content (FCF) and faecal protein content (FP) as proxies of diet quality in bears. High-FCF content indicates low diet quality, whereas high-FP content indicates high quality [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Lôbo Jr. et al (2001) reported that ADF underrated the CAD determined by total fecal collection, in contrast to Carciofi et al (1998), who deem CF and ADF efficient in this determination, but suggest the need for new studies to confirm such conclusion. Under these conditions, the reports of Vester et al (2008) and Clauss et al (2010), about the likelihood of microbial fermentation in the final portion of the small intestine and in the large intestine of small felines may justify the reduced CAD estimated by CF and ADF in the present experiment.…”
Section: Resultsmentioning
confidence: 60%
“…However, in captivity, diets are normally elaborated empirically, according to the choices and habits observed in wild animals, by trial and error and taking into account the body condition of each animal. Nevertheless, such factors may not be sufficient to attend the individual nutritional demands (Saad et al 2007, Clauss et al 2010.…”
Section: Introductionmentioning
confidence: 99%